PENERAPAN METODE AL-MIFTAH LIL ULUM DALAM MENUMBUHKAN PEMAHAMAN NAHWU SHARAF PADA SANTRI PEMULA DI PONDOK PESANTREN GUNUNG PANDAK MALANG: The Implementation of the Al-Miftah Lil Ulum Method in Fostering the Understanding of Nahw and Saraf among Beginner Students at Gunung Pandak Islamic Boarding School Malang - Riki Candra; Zainuddin Fanani (TA'LIMUNA: Jurnal Pendidikan Islam, 2026)
The teaching of Nahwu and Sharaf to beginner students at Islamic boarding schools (pesantren) still faces challenges, such as low student engagement and a predominance of theoretical teaching methods. This article examines the application of the Al-Miftah Lil Ulum Method and its contribution to fostering grammatical understanding among beginner students at the Pondok Pesantren Gunung Pandak in Malang. This article employs a descriptive qualitative approach using data collection techniques such as observation, in-depth interviews, and documentation. Data analysis was conducted using the interactive model by Miles, Huberman, and Saldana. The findings reveal that applying the Al-Miftah Method helps students systematically identify word categories, determine syntactic functions (i’rab), and analyze basic sentence structures. In addition to cognitive aspects, the application of the Al-Miftah Method increases students’ motivation and self-confidence in reading Arabic texts without vowel marks independently. Thus, the Al-Miftah Method is relevant for use as an introduction to the study of Nahwu and Sharaf in the pesantren context. Pembelajaran Nahwu dan Sharaf bagi santri pemula di pesantren masih menghadapi kendala, seperti rendahnya keterlibatan belajar dan dominasi metode yang bersifat teoretis. Artikel ini bertujuan mengkaji penerapan Metode Al-Miftah Lil Ulum dan kontribusinya dalam menumbuhkan pemahaman gramatikal santri pemula di Pondok Pesantren Gunung Pandak Malang. Artikel ini menggunakan pendekatan kualitatif deskriptif dengan teknik pengumpulan data berupa observasi, wawancara, dan dokumentasi. Analisis data melalui model interaktif Miles, Huberman, dan Saldana. Hasil penelitian menunjukkan bahwa penerapan Metode Al-Miftah membantu santri memahami identifikasi jenis kata, penentuan i’rab dan analisis struktur kalimat secara lebih sistematis. Selain aspek kognitif, penerapan Metode Al-Miftah berdampak pada meningkatnya motivasi dan kepercayaan diri santri dalam membaca teks Arab tanpa harakat secara mandiri. Jadi, Metode Al-Miftah relevan untuk dijadikan sebagai pengantar pembelajaran Nahwu dan Sharaf di pesantren. Kata Kunci : Al-Miftah Lil Ulum; Nahwu; Pembelajaran Bahasa Arab; Santri Pemula; Sharaf.